2014
DOI: 10.1161/circresaha.114.303265
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MALAT1 Regulates Endothelial Cell Function and Vessel Growth

Abstract: Rationale: The human genome harbors a large number of sequences encoding for RNAs that are not translated but control cellular functions by distinct mechanisms. The expression and function of the longer transcripts namely the long noncoding RNAs in the vasculature are largely unknown. Objective: Here, we characterized the expression of long noncoding RNAs in human endothelial cells and elucidated the function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
735
2
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(774 citation statements)
references
References 29 publications
24
735
2
13
Order By: Relevance
“…Additionally, pharmacological inhibition of MALAT1 reduced blood flow recovery and capillary density after hindlimb ischemia by impairing the expression of various cell cycle regulators. These results suggest that knockdown of MALAT1 impairs the balance of endothelial cell from a proliferative to a migratory phenotype, and further reduces vascular growth [74].…”
Section: Lncrna In Vascular Physiological or Pathological Processesmentioning
confidence: 78%
“…Additionally, pharmacological inhibition of MALAT1 reduced blood flow recovery and capillary density after hindlimb ischemia by impairing the expression of various cell cycle regulators. These results suggest that knockdown of MALAT1 impairs the balance of endothelial cell from a proliferative to a migratory phenotype, and further reduces vascular growth [74].…”
Section: Lncrna In Vascular Physiological or Pathological Processesmentioning
confidence: 78%
“…Conversely, the progression into a more severe phenotype redirects the transcriptome toward pathways biologically related with mitochondrial dysfunction21, 22 and malignancy 4, 5, 10. In this respect, MALAT1 represents a remarkable functional and versatile molecule that modulates a myriad of signaling pathways, including cell cycle control,18 immune balance,23 and endothelial cell function and vessel growth 24. These phenomena, when present concurrently, escalate in complexity to entail cell proliferation and migration,25 apoptosis, fibrosis,26 and malignancy 27…”
Section: Discussionmentioning
confidence: 99%
“…Katharina et al 51) found that MALAT1 silencing by siRNA or LNA GapmeRs induced a phenotype switch of the endothelial cells from a proliferation state to a promigratory state. This type of phenotype switch results in a block in vessel outgrowth cells and tissues such as SMCs, ECs, monocytederived macrophages, and RNA samples extracted from carotid and arterectomy 41) .…”
Section: Long Noncoding Rnas Regulate the Function Of Ecsmentioning
confidence: 99%